2016
DOI: 10.3386/w22513
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Consumption Patterns at Older Ages in the US and the UK: Can Medical Expenditures Explain the Difference?

Abstract: In this paper we document significantly steeper declines in nondurable expenditures in the UK compared to the US, in spite of income paths being similar. We explore several possible causes, including different employment paths, housing ownership and expenses, levels and paths of health status, number of household members, and out-of -pocket medical expenditures. Among all the potential explanations considered, we find that those to do with healthcare-differences in levels and age paths in medical expenses-can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…The predicted pattern of medical care expenditure and biological aging is remarkably consistent with the observed patterns of increasing budget shares for medical care over the lifetime (Banks et al, 2016), and with the evidence on the dynamics of hazard rates observed in supercentenarians (Barbi et al, 2018). In particular, note that our model of deficit accumulation with uncertain lifetime does not change the main predictions from the standard health deficit model that medical care increases with age, a prediction in line with observable life time pattern of medical care (e.g.…”
Section: Solving the Modelsupporting
confidence: 76%
“…The predicted pattern of medical care expenditure and biological aging is remarkably consistent with the observed patterns of increasing budget shares for medical care over the lifetime (Banks et al, 2016), and with the evidence on the dynamics of hazard rates observed in supercentenarians (Barbi et al, 2018). In particular, note that our model of deficit accumulation with uncertain lifetime does not change the main predictions from the standard health deficit model that medical care increases with age, a prediction in line with observable life time pattern of medical care (e.g.…”
Section: Solving the Modelsupporting
confidence: 76%
“…To the best of our knowledge, this is the first paper to report estimates of a life-cycle consumption profile for Portuguese households allowing for time and cohort effects. We find a much flatter life-cycle consumption profile than the profiles reported in the literature for other countries-see, e.g., Alessie and Ree (2009) for the Netherlands, Banks et al (2016) for the UK, and Gourinchas and Parker (2002), Aguiar and Hurst (2013) and Fernández-Villaverde and Krueger (2007) for the USA.…”
Section: Introductioncontrasting
confidence: 55%
“…In this sense, our results are closer to what the life-cycle theory of consumption predicts. However, consumption of older households, namely those over sixty years old, tends to decrease, as has been reported in the literature-see, e.g., Banks et al (1998) and Banks et al (2016).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several papers (De Nardi et al 2010, Kopecky and Koreshkova 2014, Ameriks et al (2015 show that health care costs that rise with age and income explain much of the U.S. elderly's saving behavior. 1 Differences in medical spending risk are also important in explaining cross country differences in the consumption (Banks et al, 2016) and savings decisions (Nakajima and Telyukova, 2018) of elderly households. More generally, the literature on the macroeconomic implications of health and medical spending is growing rapidly.…”
Section: Introductionmentioning
confidence: 99%